Collective action for smallholder market access: evidence and implications for Africa - Markelova, H.; Mwangi, E. (2010)
It is widely acknowledged that the involvement of small farmers into markets can contribute to higher productivity and income growth, which in turn can enhance food security, poverty reduction efforts, and overall economic growth. In Africa, as in other parts of the developing world, agricultural production systems and their participants face significant challenges as a result of changing economic, environmental, and sociopolitical context. New dynamics in the global agricultural economy, such as the growth of supermarkets, are providing smallholders with both the new opportunities and new constraints to participate in and benefit from market exchanges. Collective action in the form of producer groups can enable African smallholders to take advantage of the new value chains and deal with existing market imperfections. However, certain conditions must be in place to create and sustain incentives for farmers to organize around marketing. Experiences from collective action in natural resource management (NRM) have shown that the types of markets and products, characteristics of user groups, institutional arrangements, and external environment need to be considered in order to determine the effectiveness and sustainability of collective marketing for smallholders. This paper applies the lessons from collective action in NRM to marketing, using existing case studies of producer groups in Africa, and offers policy recommendations on the factors that contribute to the success of collective marketing efforts.